PERSEPSI MAHASISWA PADA MATAKULIAH DASAR UMUM (MKDU) - Ahmadi Ahmadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
General Basic Course (GBC) is often a dilemma for students. On one hand, its presence is considered important by the majority of students while on the other side of existence is considered a mere formality to meet graduation requirements. Actual GBC can be said is important, but also can also be said to be important, depending on which side of the saw GBC considered important, because GBC has the objective, among others, to establish an undergraduate student as a candidate who is not only competent in the field of education that they do, but also equipped with the basic -Basic education and mental shape a good personality. This study was conducted to determine the interest and response of Management students University of Batanghari of the existence of GBC and student response against all four subjects GBC (Pancasila education, Civics, Indonesian, and English). This study uses a quantitative approach with descriptive research and survey research methods. The results showed that students' perceptions of management in 2012 and 2013 University of Batanghari against GBC found that the subjects of the most desirable and most important is considered English subjects. Whereas the general basic subjects of the most disliked and most are not considered important is Citizenship Education course, and there is no dependency between the force with the response of students to courses Pancasila education, Civics, Indonesian, and English. That is the second student response force (2012 and 2013) against the four GBC are the same.Key Word: General Basic Course (Pancasila education, Civics, Indonesian, and English